Pengaruh Kepemimpinan Dan Motivasi Kerja Terhadap Kinerja Pegawai Di Dinas Perkebunan Provinsi Sumatera Selatan - Utari, Karmila; Darwin, Darwin (Jurnal Keuangan dan Bisnis, 2023)
This study aims to analyze the influence of leadership and motivation on employee performance at the South Sumatra Plantation Department during the Covid 19 pandemic. The samples, 70 respondents, are the employees of the South Sumatra Plantation Department and primary data collected by distributing questionnaires to all respondents. The results reveal that hypotheses 1, 2, and 3 are accepted. The accepted hypothesis 1 implies that there is a is a significant influence of leadership on employee performance. Meanwhile, the accepted hypothesis 2 infers that there is a significant influence of work motivation on employee performance. In addition, the accepted hypothesis indicates that there is an influence of leadership and work motivation on employee performance.